Human Papillomavirus Typing on Different Clinical Morphologies of Condyloma Acuminatum - Sri Katon Sulistyaningrum; Taris Zahratul Afifah (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2026)
Background: Low-risk human papillomavirus (HPV) types 6 and 11 are estimated to cause around 90% of genital warts. However, data on HPV type distribution in different CA morphologies are lacking in Indonesia. Purposes: This study aimed to identify HPV types across various clinical manifestations of CA. Method: A cross-sectional study was conducted at the Dermato-Venereology Clinic, Dr. Cipto Mangunkusumo National Hospital, Jakarta. A total of 37 patients were enrolled, yielding 40 DNA samples from 40 CA lesions. Result: HPV genotyping was performed using PCR and dot blot hybridization with the HPV Express Matrix®, capable of detecting 21 low- and high-risk HPV types and identifying multiple types within a single specimen. HPV DNA was detected in 34 of 40 lesions (85%). Four clinical manifestations of CA were documented: classic type (26/40, 65%), keratotic papules (2/40, 5%), smooth papules (9/40, 22.5%), and flat-top papules or plaques (3/40, 7.5%). Low-risk HPV types (6, 11, 42, 43) were identified in 28 lesions (70%), with HPV 6 and 11 being most common. High-risk HPV types (16, 31, 35, 39, 45, 52, 56, 66, 68) were detected in some lesions, either singly or in co-infection with low-risk types. Notably, high-risk HPV type 52 was found in keratotic and flat-top papules. Conclusion: This is the first study in Indonesia to identify HPV types in CA lesions of varying morphology. While low-risk HPV types remain predominant, the presence of high-risk HPV in a subset of lesions highlights the need for vigilance regarding potential malignant transformation.